1997
DOI: 10.1017/s0033822200018579
|View full text |Cite
|
Sign up to set email alerts
|

New 14C Dating of the Archaic Royal Necropolis Umm El-Qaab at Abydos (Egypt)

Abstract: Since 1977, the German Institute of Archaeology in Cairo has been reexamining the archaic Royal necropolis Umm el-Qaab at Abydos (ca. 500 km south of Cairo). The necropolis consists of the tomb complexes of six kings and one queen of Dynasty I as well as two kings of Dynasty II in the southern part, the cemetery with royal tombs from Dynasty 0 and early Dynasty I in the middle and the predynastic cemetery in the northern part. Although partly destroyed and deprived of most of their contents, the tombs and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Many archaeologists studying the Ancient Near East have claimed (or complained) that radiocarbon dates are earlier than archaeo-historical dates for the early historical period: for Egypt (Görsdorf et al 1998;Bonani et al 2001), Sumer (Crawford 1991), Israel-Palestine (Bruins and van der Plicht 2001;Mazar 1992), Italy (Guidi and Whitehouse 1996), and the Aegean (Dickinson 1994), among others. Indeed, in a 2001 issue of Radiocarbon that was devoted to Ancient Near Eastern chronology, the introductory survey paper concluded that the "Collective evidence … clearly indicates … major chronological" disparities between 14 C and archaeo-history for the early historical period (Bruins 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Many archaeologists studying the Ancient Near East have claimed (or complained) that radiocarbon dates are earlier than archaeo-historical dates for the early historical period: for Egypt (Görsdorf et al 1998;Bonani et al 2001), Sumer (Crawford 1991), Israel-Palestine (Bruins and van der Plicht 2001;Mazar 1992), Italy (Guidi and Whitehouse 1996), and the Aegean (Dickinson 1994), among others. Indeed, in a 2001 issue of Radiocarbon that was devoted to Ancient Near Eastern chronology, the introductory survey paper concluded that the "Collective evidence … clearly indicates … major chronological" disparities between 14 C and archaeo-history for the early historical period (Bruins 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Of some 370 published examples from Abydos, almost 200 come from a Predynastic / Later Predynastic cemetery (U) at this site, most being found in and around the large multi-chambered tomb U-j (Dreyer 1998). These have been dated to the Naqada IIIA1 cultural phase (c.3300 / 3100 bce; Boehmer et al 1993;Görsdorf et al 1998). The remainder date from the Naqada IIICearly D cultural phases (c.3100-2770 bce), or the entire 1 st Dynasty.…”
Section: Inscribed Labelsmentioning
confidence: 99%
“…Of some 370 published examples from Abydos, almost 200 come from a Predynastic / Later Predynastic cemetery (U) at this site, most being found in and around the large multi-chambered tomb U-j . These have been dated to the Naqada IIIA1 cultural phase (c.3300 / 3100 bce; Boehmer et al 1993;Görsdorf et al 1998). The remainder date from the Naqada IIICearly D cultural phases (c.3100-2770 bce), or the entire 1 st Dynasty.…”
Section: Inscribed Labelsmentioning
confidence: 99%